2017
DOI: 10.3389/fpls.2017.00193
|View full text |Cite
|
Sign up to set email alerts
|

Selection of Candidate Reference Genes for Gene Expression Analysis in Kentucky Bluegrass (Poa pratensis L.) under Abiotic Stress

Abstract: Kentucky bluegrass (Poa pratensis L.) belong to Gramineae and is widely used in lawns, golf courses, landscapes, and sport fields as a prominent cool-season grass. Gene expression patterns during different stages of plant development can provide clues toward the understanding of its biological functions. The selection and validation of reference genes are the first steps in any real-time quantitative PCR gene expression study. Therefore, suitable reference genes are necessary for obtaining reliable results in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 38 publications
2
39
1
Order By: Relevance
“…Total RNA was extracted from non-stressed and stressed root tissues of two alfalfa varieties with three biological replicates (each containing 100 mg alfalfa roots) using the RNA simple Total RNA Kit (TIANGEN BIOTECH, Co., Ltd, Beijing, China) based on the kit instructions. cDNA was reverse transcribed from 1 μg of total RNA using a First Strand cDNA Synthesis Kit (TaKaRa, Dalian, China) ( Niu et al, 2017 ). Specific RT-qPCR primers were designed using Primer 3 4 ( Table 1 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Total RNA was extracted from non-stressed and stressed root tissues of two alfalfa varieties with three biological replicates (each containing 100 mg alfalfa roots) using the RNA simple Total RNA Kit (TIANGEN BIOTECH, Co., Ltd, Beijing, China) based on the kit instructions. cDNA was reverse transcribed from 1 μg of total RNA using a First Strand cDNA Synthesis Kit (TaKaRa, Dalian, China) ( Niu et al, 2017 ). Specific RT-qPCR primers were designed using Primer 3 4 ( Table 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…Each 20 μL reaction mixture contained 2 μL template cDNA, 10 μL of 2× SYBR ® Premix Dimer Eraser, 0.8 μL of each primer (10 μM), 6.0 μL dd H 2 O, and 0.4 μL of ROX reference Dye. The amplification reaction conditions were as follows: 95°C for 3 min followed by 40 cycles of 95°C for 10 s and 60°C for 30 s ( Niu et al, 2017 ). The levels of relative gene expression were calculated by the ddCt algorithm using the alfalfa MtGAPDH gene as the housekeeping gene ( Zhang et al, 2003 ).…”
Section: Methodsmentioning
confidence: 99%
“…The specific primers of C-repeat binding factors (CBFs) were designed according to Zhang et al [70]. In qRT-PCR analysis of CBFs, Actin gene was used as an internal control [71], the expression data were normalized to the control conditions (set at 1), using the comparative threshold cycle method. Each experiment included three independent biological replicates.…”
Section: Analysis Of Physiological and Cbfs Expression Levelsmentioning
confidence: 99%
“…Total RNA was extracted from the control and cold groups of the two genotypes using The relative level of gene expression was calculated using the 2 −ΔΔct formula [82]. The P.pratensis putative Actin gene was used as an endogenous control [71]. The specific primers (Additional file 6: Expression patterns of selected genes involved in cold stress in two P.pratensis cultivars.…”
Section: Quantitative Real-time Pcr (Qrt-pcr) Validationmentioning
confidence: 99%
“…Constitutively expressed housekeeping genes are transcribed at a relatively constant level, and are usually selected for this purpose [ 18 , 19 ], because their expression is generally assumed to be minimally affected by experimental conditions. However, recent studies have shown that housekeeping genes that are commonly used as reference genes may not be as consistently expressed as previously thought [ 20 23 ], and can vary according to plant species, tissue type, and environmental conditions [ 24 ]. The use of non-validated references genes can therefore result in inaccurate quantification of miRNA expression when comparing samples from different sources.…”
Section: Introductionmentioning
confidence: 99%